Cornicle secretions of Uroleucon nigrotuberculatum (Homoptera: Aphididae) as the last bullet against lady beetle larvae. Issue 4 (6th July 2016) - Barry, Adema; Ohno, Kazuro
Abstract: Aphids have evolved various defense strategies against natural enemies, including secretions from their cornicles. We assessed the defensive function of cornicle secretions by the goldenrod aphid, Uroleucon nigrotuberculatum (Olive), against larvae of the lady beetles Coccinella septempunctata bruckii Mulsant and Propylea japonica (Thunberg) (Coleoptera: Coccinellidae). The aphid secreted red droplets from its cornicles when attacked by the larvae. Two‐thirds of the C. septempunctata bruckii larvae and 46.7% of the P. japonica larvae that preyed on the aphids died before reaching the pre‐pupal stage. The secretions caused molting failure when smeared on the larvae's heads or glued to the larvae's mouthparts, killing 56.7% of C. septempunctata bruckii larvae and 36.7% of P. japonica larvae. Second instar larvae were affected most. About 40% of third and fourth instar larvae of C. septempunctata bruckii vomited soon after ingesting the aphids. In the field, up to 40% of first and second instar larvae were smeared with red secretions. Our results show that these cornicle secretions are an effective and active defense against earlier instars of coccinellid larvae. Abstract : Aphid cornicle secretion works as physical defense against lady beetles. The lady beetle larvae effectively smeared with such secretion often failed in molting and subsequently died. Field observations revealed that secretion is lethal to lady beetles.